Why American Foreign Policy Fails Unsafe at Home and Despised Abroad - Jett, D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This book explores the recent changes in U.S. foreign policy, examines the roles that the six primary actors (the President, the Congress, the bureaucracy, non-governmental organizations, the media and the public) play in policy decisions, and assesses the potential for improvement within this system.
Keywords: Europe—Politics and government; International relations; Political science; European Politics; International Relations; Political Science; Foreign Policy